2011
DOI: 10.1002/adfm.201100659
|View full text |Cite
|
Sign up to set email alerts
|

Length‐Scale Mediated Differential Adhesion of Mammalian Cells and Microbes

Abstract: Surfaces of implantable biomedical devices are increasingly engineered to promote their interactions with tissue. However, surfaces that stimulate desirable mammalian cell adhesion, spreading, and proliferation also enable microbial colonization. The biomaterials‐associated infection that can result is now a critical clinical problem. We have identified an important mechanism to create a surface that can simultaneously promote healing while reducing the probability of infection. Surfaces are created with submi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 45 publications
1
68
0
Order By: Relevance
“…) of PEG thin films lead to the formation of features patterned on the underlying silicon substrate. We have previously shown that these features swell when immersed in water in a dose‐dependent manner and thus correspond to microscopic hydrogels (microgels). Immunofluorescence imaging (see below and elsewhere demonstrates that these features resist protein adsorption consistent with hydrated PEG gels and brushes.…”
Section: Resultsmentioning
confidence: 95%
“…) of PEG thin films lead to the formation of features patterned on the underlying silicon substrate. We have previously shown that these features swell when immersed in water in a dose‐dependent manner and thus correspond to microscopic hydrogels (microgels). Immunofluorescence imaging (see below and elsewhere demonstrates that these features resist protein adsorption consistent with hydrated PEG gels and brushes.…”
Section: Resultsmentioning
confidence: 95%
“…Tibial nail 1-7 ( 8) microbial colonization. Notably, surface modification remains the most frequently adopted route to reduce the incidence of biomaterial-associated infection (28)(29)(30). Unfortunately, performance demands and expectations imposed on many coatings by clinicians and patients to address infection risks are ill-defined.…”
Section: Protecting the Primary Implant Patientmentioning
confidence: 99%
“…Nanotechnology also offers some promise with regard to minimizing the burden of implant‐associated infections, as reviewed by Montanaro [53]. Techniques such as micropatterning of antifouling surfaces have shown that bacterial‐repellent and tissue‐friendly surfaces may be achieved [54]. Similarly, nanoparticles other than silver have also been investigated for antibacterial efficacy.…”
Section: Designing Surfaces To Combat Infectionmentioning
confidence: 99%